Long-term outcomes of group B streptococcal meningitis - Libster, Romina; Edwards, Kathryn M; Levent, Fatma; Edwards, Morven S; Rench, Marcia A; Castagnini, Luis A; Cooper, Timothy; Sparks, Robert C; Baker, Carol J; Shah, Prachi E (Pediatrics (Evanston), 2012)
Group B Streptococcus (GBS) is the leading cause of meningitis in young infants. We evaluated long-term outcomes among GBS meningitis survivors. We hypothesized that despite reduced mortality, GBS meningitis would remain a significant cause of morbidity among GBS survivors. Ninety term and near-term infants diagnosed with GBS meningitis from 1998 through 2006 were identified from 2 children's hospitals. Five died acutely, and 5 died at 6 months to 3 years of age. Forty-three survivors (54%; mean age 6.8, range 3-12 years) were consented for evaluation and underwent physical and neurologic examinations, hearing and vision screening, and standardized developmental assessments. Associations among presenting features, laboratory parameters, neurologic status at hospital discharge, and later developmental outcomes were explored by using descriptive statistics and logistic regression. Twenty-four of 43 (56%) children evaluated demonstrated age-appropriate development, 11 (25%) had mild-to-moderate impairment, and 8 (19%) had severe impairment. Admission features associated with death after hospital discharge or severe impairment included lethargy (P = .003), respiratory distress (P = .022), coma or semicoma (P = .022), seizures (P = .015), bulging fontanel (P = .034), leukopenia (P = .026), acidosis (P = .024), cerebrospinal fluid protein >300 mg/dL (P = .006), cerebrospinal fluid glucose <20 mg/dL (P = .026), and need for ventilator (P = .002) or pressor support (P < .001). Features at discharge associated with late death or severe impairment included failed hearing screen (P = .004), abnormal neurologic examination (P < .001), and abnormal end of therapy brain imaging (P = .038). Survivors of GBS meningitis continue to have substantial long-term morbidity, highlighting the need for ongoing developmental follow-up and prevention strategies such as maternal immunization.